Overcoming the Liability of Foreignness - Zaheer, Srilata (Academy of Management Journal, 1995)
This study addressed the question of whether firms in a competitive, globally integrated environment face a "liability of foreignness " and to what extent either importing home-country organizational capabilities or copying the practices of successful local firms can help them over-come this liability. Predictions were tested with a paired sample of 24 foreign exchange trading rooms of major Western and Japanese banks in New York and Tokyo. Results support the existence of a liability of foreignness and tbe role of a firm's administrative beritage in providing competitive advantage to its multinational subunits. They also highlight the difficulty firms face in copying organizational practices from other firms. Researchers in international business have long theorized that multina-tional enterprises (MNEs) doing business abroad face costs (Hymer, 1976; Kindleberger, 1969) arising from the unfamiliarity of the environment, from cultural, political, and economic differences, and from the need for coordi-nation across geographic distance, among other factors. This liability of for-eignness has been the fundamental assumption driving theories of the mul-tinational enterprise (Buckley & Casson, 1976; Caves, 1982; Dunning, 1977; Hennart, 1982). Further, it has been argued that to overcome the liability of foreignness and compete successfully against local firms, MNEs need to provide their overseas subunits with some firm-specific advantage, often in the form of organizational or managerial capabilities (Buckley & Casson,